Research of energy consumption of livestock complexes using methods of systematic bioenergy analysis - Chmil, A.; Sinyavsky, O.; Savchenko, V. (Energy and Automation, 2026)
Solving the food problem in Ukraine is impossible without further increasing the production of livestock products, and, consequently, the construction of new, reconstruction and improvement of the efficiency of operation of existing livestock complexes with industrial technology and a high level of electrification and automation of production processes. Considering agriculture as a system where the conversion and accumulation of solar and other types of energy into food takes place using plants and animals, the problem of energy efficiency of agricultural production must be solved on the basis of a comprehensive analysis of energy consumption not only within each sphere, but also the entire energy flow of the agricultural complex. The constant growth of energy resource consumption with a simultaneous decrease in their supply, unjustifiably large and irrational consumption of electricity, fuel and feed, characteristic of many branches of agriculture and, above all, animal husbandry, a significant increase in the cost of energy resources and other reasons have determined the importance and relevance of energy-saving policy. Increasing the level of rational use of energy resources in agricultural production is of great importance and is characterized by significant savings in material and energy resources. Thus, saving only 1% of energy resources in Ukrainian agriculture is equivalent to saving 8700 GJ per year. Therefore, the task of optimal management of energy consumption in agriculture should be considered as an alternative to the development of generating capacities. System bioenergy analysis significantly exceeds the capabilities of technical and economic analysis to identify reserves of saving fossil energy resources. If in the process of conducting a technical and economic analysis, shortcomings and their causes are identified, then the result of a system analysis is the search for specific ways to eliminate these shortcomings and increase the efficiency of the functioning of the object under study. Recieved: 02.02.2026. Recieved: 26.03.2026. Accepted: 17.04.2026.